(untitled) (Academic Journal of Internal Affairs, 2020)
From a psychological point of view, there are different theories about the connection of alcohol consumption and violent behaviour (Bácskai, 2006). According to the researches in the topic, alcohol consumption increases the risk of crime and there is a very strong connection between alcohol consumption and violent crime. The question is, to which extent could be the role of alcohol in committing crime in a violent way and what mechanisms can be defined in the context of alcohol and violent behaviour (Lévay, 2006).